2018
DOI: 10.1590/0101-60830000000159
|View full text |Cite
|
Sign up to set email alerts
|

The effect of obsessive compulsive symptoms on psychopathology in patients with schizophrenia

Abstract: Background: There is a growing interest on the impact of comorbid obsessive-compulsive symptoms (OCS) on the course and severity of schizophrenia in recent years. Objectives: This study determined the prevalence of OCS in schizophrenia patients and the clinical outcomes of the comorbidity. Methods: A total of 220 schizophrenia patients were recruited. All the participants completed Structure Clinical Interview version, Yale Brown Obsessive Compulsive Scale, Calgary Depression Scale for Schizophrenia, Columbia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
(66 reference statements)
1
4
0
Order By: Relevance
“…Patients with schizophrenia who develop OCD showed worse functioning as measured by significantly lower wellbeing scores (as subjectively scored by the patients themselves). This is in concordance with previous work (De Haan et al, 2013, Seng et al, 2018, Üçok et al, 2014), which used self rated scales to assess quality of life. In our study, a clinician-scored GAF scale was also used.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Patients with schizophrenia who develop OCD showed worse functioning as measured by significantly lower wellbeing scores (as subjectively scored by the patients themselves). This is in concordance with previous work (De Haan et al, 2013, Seng et al, 2018, Üçok et al, 2014), which used self rated scales to assess quality of life. In our study, a clinician-scored GAF scale was also used.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, studies investigating patient outcome and level of functioning in antipsychotic induced OCD are sparse and need further clarification (De Haan et al, 2013, Frias et al, 2014, Kim et al, 2015, Mukhopadhaya et al, 2009, Seng et al, 2018, Üçok et al, 2014). Studies have shown lower scores in self rated and foreign rated measures of wellbeing in those cases with antipsychotic-induced OCD compared to those without, with higher depressive symptoms, suicidality, hospitalisation, poorer physical and psychological health (De Haan et al, 2013, Kim et al, 2015, Seng et al, 2018, Üçok et al, 2014). In addition, interpersonal relationship scores were lower in those with OCD (Üçok et al, 2014) and OCD cases may also show more motor symptoms (Mukhopadhaya et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…That outcome demonstrated a significant association between the OCD comorbidity and the severity of clinical features in patients with schizophrenia, as has been reported in previous studies. 12 - 15 …”
Section: Discussionmentioning
confidence: 99%
“…That outcome demonstrated a significant association between the OCD comorbidity and the severity of clinical features in patients with schizophrenia, as has been reported in previous studies. [12][13][14][15] Although the difference in the severity of clinical characteristics between the patients with OCS, and OCD was not statistically significant, those with OCD comorbidity had higher clinical scores. In addition, there was a significant relationship between the severity of obsessive-compulsive symptoms and psychotic features in the patients with OCD comorbidity, nevertheless, a similar relationship was not determined in those with OCS, and without OCD.…”
Section: Sociodemographicmentioning
confidence: 92%
See 1 more Smart Citation